Violence against Health-Care Workers in Governmental Health Facilities in Arar City, Saudi Arabia - Ruqayyah B. Al Anazi; Saeed M. AlQahtani; Amal E. Mohamad; Sabry M. Hammad; Hossam Khleif (The Scientific World Journal)
Background. Violence against health-care workers (HCWs) showed increasing worldwide concern. No previous studies addressed violence against HCWs in the Northern region, Saudi Arabia. Objectives. To determine the prevalence of violence against HCWs in public hospitals and primary health-care centers in Arar city, KSA, and to identify its associated factors. Methods. A cross-sectional study was conducted on 352 HCWs in the Ministry of Health (MOH) facilities in Arar city from 1st October to 31st December 2018. Consented HCWs completed a structured self-administered questionnaire which was modified from the WHO questionnaire for violence. Results. Out of 352 health-care workers, 171 (48.6%) reported exposure to violence during work in the past year. The verbal violence was the most common form experienced (83%). Physicians were the main exposed group (59%). Being non-Saudi HCWs, older with longer duration of experience, working in hospitals, working in the emergency room, and working in evening or night shifts were significantly associated with more exposure to violence. The unmet demand for the patient and deficient staff number were the leading reasons for aggression. Only 16.4% of assaulted HCWs reported the violent acts to the higher health affairs authority with the most frequent reasons for nonreporting were their perception that it was useless and their fear of negative consequences. Conclusions. Violence against HCWs in Arar city, KSA, is a prevalent problem. Improving health security system and increasing staffing and their training on proper dealing with violence are highly recommended. Also, enforcing rules and regulations is an important demand to control and prevent violence against HCWs.